2020
DOI: 10.3892/br.2020.1281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes in gastric cancer using bioinformatics analysis

Abstract: Gastric cancer (GC) is one of the most common types of cancer worldwide. Patients must be identified at an early stage of tumor progression for treatment to be effective. The aim of the present study was to identify potential biomarkers with diagnostic value in patients with GC. To examine potential therapeutic targets for GC, four Gene Expression Omnibus (GEO) datasets were downloaded and screened for differentially expressed genes (DEGs). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…CST1 and CST4 were previously reported to be oncogenes (Jiang et al, 2018;Cui et al, 2019;Liu et al, 2019;Wang et al, 2020). Next, we studied the role of CST1 and CST4 in thyroid carcinoma.…”
Section: Depletion Of Cst1 But Not Cst4 Inhibits Proliferation and Invasion And Promotes Apoptosismentioning
confidence: 98%
See 2 more Smart Citations
“…CST1 and CST4 were previously reported to be oncogenes (Jiang et al, 2018;Cui et al, 2019;Liu et al, 2019;Wang et al, 2020). Next, we studied the role of CST1 and CST4 in thyroid carcinoma.…”
Section: Depletion Of Cst1 But Not Cst4 Inhibits Proliferation and Invasion And Promotes Apoptosismentioning
confidence: 98%
“…CST1 (cystatin 1), a type 2 cystatin superfamily member, is a specific inhibitor of cysteine proteases (Dai et al, 2017;Oh et al, 2017;Jiang et al, 2018;Liu et al, 2019). Several studies demonstrated that CST1 was closely associated with cell proliferation and metastasis in various cancers, including cancer of the stomach, breast, colorectum, pancreas, and bile duct (Jiang et al, 2018;Cui et al, 2019;Liu et al, 2019;Wang et al, 2020). Wang et al (2020) predicted that CST1 was a biomarker and therapeutic target for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The β subunits were coded using ATP4B genes [24] . Many studies have revealed that ATP4B expression is decreased in human gastric cancer(GC) [25][26][27][28] , and some studies have reported abnormal expression of ATP4B in other diseases such as human hepatocellular carcinoma(HCC) [29] , laryngopharyngeal re ux, and laryngeal cancer [30] . However, to date, there are no studies about the relationship between this gene and EPN-PF.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the standard diagnostic method, esophagogastroduodenoscopy, is an invasive and expensive procedure which has resulted in late diagnosis and an average 5-year survival of ~30%. Therefore, elucidating the molecular basis of GC has become crucial to developing timely diagnostic and therapeutic strategies [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%